2013
DOI: 10.1038/srep02606
|View full text |Cite
|
Sign up to set email alerts
|

Distinct cell shapes determine accurate chemotaxis

Abstract: The behaviour of an organism often reflects a strategy for coping with its environment. Such behaviour in higher organisms can often be reduced to a few stereotyped modes of movement due to physiological limitations, but finding such modes in amoeboid cells is more difficult as they lack these constraints. Here, we examine cell shape and movement in starved Dictyostelium amoebae during migration toward a chemoattractant in a microfluidic chamber. We show that the incredible variety in amoeboid shape across a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
103
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(109 citation statements)
references
References 33 publications
6
103
0
Order By: Relevance
“…Other groups have reported that migrating fish keratocytes and Dictyostelium cells also exist in a low‐dimensional shape space. Despite their different origins, many cell lines adopt shapes that are strikingly similar.…”
Section: How Many Cell Shapes Are There?mentioning
confidence: 99%
“…Other groups have reported that migrating fish keratocytes and Dictyostelium cells also exist in a low‐dimensional shape space. Despite their different origins, many cell lines adopt shapes that are strikingly similar.…”
Section: How Many Cell Shapes Are There?mentioning
confidence: 99%
“…The seemingly endless variety of cell shape seen in chemotaxis can be reasonably well described mathematically by just three principal components, representing cell elongation, cell polarisation and pseudopod splitting or bending [6 ]. Cells adopt characteristic shapes according to the strength (signal/noise) of the chemotactic gradient: in strong gradients they tend to be wedge shaped and move quickly, whereas in weak gradients they typically alternate between pseudopod splitting and cell elongation.…”
Section: Modes and Mechanics Of Movementmentioning
confidence: 99%
“…Early observations in Dictyostelium and neutrophils suggested that small membrane protrusions, called filopodia, preferentially form towards the external gradient [48,49]. Stochastic cell-shape changes in response to gradients may thus act as an additional layer regulating the dynamics of the polarised assembly [50,51]. The increased local membrane area increases the local receptor concentration, and thus likely enhances polarised assembly recruitment locally.…”
Section: Substrate Limitation As Efficient Global Inhibitor In Local mentioning
confidence: 99%